Avaliação de conectividade em sistemas orientados por objetos - Kecia Aline Marques Ferreira (2006)
Amongst the factors of software quality evaluation , maintainability, the measure of the easiness to carry through its maintenance, distinguishes. Software maintenance is mostly responsible for the total system cost. In such a way, the attainment of resources that contribute for the software creation whose maintenance is easier becomes important. Amongst other aspects, the development of software with this characteristic is achieved mainly by means of software project that aims at flexible and stable structure, in which the interdependence degree between the constituent parts of software, their modules, is minimized. How much bigger the degree of connectivity in a software, more rigid is its structure, minor maintainability and greater the cost of the system. This work has as thesis that the connectivity is the main factor in the evaluation of the structural quality of a software and, consequently, may be taken as factor of great importance in the maintenance and the cost of a system. The aim of this work is the proposal of a model of evaluation of connectivity in object-oriented software, as well as the construction of an automatic tool for metric collection that it makes possible the application of the aforesaid model for software implemented in the Java language.